Effects and moderators of the Olweus bullying prevention program (OBPP) in Germany - Ossa, Fanny; Jantzer, Vanessa; Eppelmann, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (European child & adolescent psychiatry, 2021)
Bullying is a common and significant risk factor for mental and physical health problems. The aim of the outlined study was to evaluate the German version of the Olweus Bullying Prevention Program (OBPP) and to investigate potential moderators of its effectiveness. 23 schools started with the implementation and all students were invited to complete the Olweus Bullying Questionnaire annually. For our analyses, the data from grades 5 to 9 were used (t0: n = 5759; t1: n = 5416; t2: n = 4894). 16 out of the 23 schools completed the 18-months implementation period. The effectiveness of the program statistically depended on its complete implementation (χ2(2) = 7.62, p = 0.022). In the group of non-completers, the prevalence of victimization did not change during the observation period of 2 years (χ2(2) = 4.64, p = 0.099). In the group of the completer schools, a significant decrease in bullying between t0 and t1 was found for victims (t0: 9.14%; t1: 6.87%; OR = 0.74; 95% CI 0.62-0.88; p = 0.001) and perpetrators (t0: 6.16%; t1: 4.42%; OR = 0.70; 95% CI 0.55-0.89; p = 0.004). After 24 months (t2), this decrease could be retained (victims: t2: 6.83%; OR = 0.73; 95%CI = 0.61-0.88; p = 0.001; perpetrators: t2: 4.63%; OR = 0.72; 95% CI 0.57-0.92; p = 0.009). Furthermore, we found the following moderators of program effectiveness in the completer schools: (1) gender (with a stronger decrease among victimized girls; p = 0.004) and (2) school grade (with a stronger decrease of victimization among grades 5-7; p = 0.028). The German version of the OBPP significantly reduced the bullying prevalence in the completer schools. Effective prevention needs time and resources: fulfilling the 18-months implementation period was the basis for positive results.
Published: 22 September 2020
Gesehen am 11.11.2021